Continuity and growth: key considerations in the improvement and standardization of the department of Arabic language and literature postgraduate programs - Hj. Yaakub, Muhamadul Bakir (s.n, 2013)
This research is an attempt to address the issue of exemplary post graduate programs in the field of Arabic studies offered by the Department of Arabic language and literature, International Islamic University Malaysia (IIUM) as an institution established outside Arabian homelands. The objective of this study is to describe the structural outstanding and the exemplary academic specialization of the field. The data of this study is obtained from the programs study plan, courses outline and also teaching materials used in the classroom. Through observational analysis, the criteria of excellence and exemplary was identified and classified. Indeed, the existence of a post graduate program in the area of globalization is very fundamental issue to the aspirations of a developing country in imitating the achievement secured by the developed countries in term of academic specialization and innovative upscale. Thus, it was assumed when a student was able to continue the study to this level, then he/she will able to choose a specialization that he/she wants to become a specialist in it with full conviction, abilities, talents, performances and in accordance to needs of his/her time. It is logical that we wonder, in the case of the inability of the student to achieve this exemplary state of specialization how we can achieve the cultural growth, scientific development and modernity? It is noted that this situation will not occur in a vacuum of space, but rather stem from the surrounding reality and background whether culturally, social and psychologically. The finding of fieldwork data analysis collected within the department of Arabic Language and Literature at the International Islamic University Malaysia represents an important experience with regard to the issue of post graduate programs offered within Malaysia contextual situation